2020
DOI: 10.1177/0268355520962920
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and clinical results after endovascular sclerotherapy: A comparison between intra- and extramuscular low-flow venous malformations

Abstract: Background Based on clinical observations we hypothesized that patients with intramuscular venous malformations (VMs) did worse or needed more sclerotherapy sessions than patients with extramuscular VMs. Purpose To evaluate the difference in treatment and quality of life (QOL) results after Polidocanol sclerotherapy of intra- and extramuscular low-flow VMs. Material and methods Forty-one patients with a VM were treated with Polidocanol in two university hospitals. The results were retrospectively analyzed. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…17 Several publications report there is a discrepancy between radiologic and clinical outcomes after VM sclerotherapy. 7,[11][12][13]18 Bianchini, G et al reported significant improvement in the symptoms in intramuscular VMs with sclerotherapy even when 83.9% of the posttreatment MRI showed no significant change of the VMs. 11 Cure is rarely possible in VM treatment and the main concept in VM treatment is palliation of the patient's symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…17 Several publications report there is a discrepancy between radiologic and clinical outcomes after VM sclerotherapy. 7,[11][12][13]18 Bianchini, G et al reported significant improvement in the symptoms in intramuscular VMs with sclerotherapy even when 83.9% of the posttreatment MRI showed no significant change of the VMs. 11 Cure is rarely possible in VM treatment and the main concept in VM treatment is palliation of the patient's symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Clinical and radiological responses do not always correlate in VMs treatment, symptomatic relief can be achieved even when there is no improvement in the imaging findings. [11][12][13] Hence, improvement in clinical symptoms reported by the patients has a crucial role in the assessment of treatment response. 12 This study aimed to evaluate the clinical results of polidocanol sclerotherapy regarding patient perceived improvement and patient satisfaction after treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in another study of 41 patients who underwent sclerotherapy of VMs with polidocanol, there was no statistically significant difference in quality of life, pain, or functional limitations between those with intramuscular lesions versus those with extramuscular lesions. 26 For LMs, a review of several studies found that sclerotherapy alone is highly effective in the treatment of macrocystic lesions, while surgery, with or without combination sclerotherapy, is more effective in the treatment of microcystic and mixed lesions.…”
Section: Clinical Outcomes and Complicationsmentioning
confidence: 99%